KETIDAKSEIMBANGAN MANAJEMEN ORGANISASI MODERN: ANALISIS ISI QUR'ANI UNTUK FALAH BERKELANJUTAN - Yuli Supodo; Ahmad Zain Sarnoto (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
Modern organizational management rooted in secular Western paradigms has succeeded in improving efficiency through planning, organizing, directing, and controlling functions. However, this approach often neglects ethical and spiritual dimensions, leading to corruption, unhealthy bureaucracy, and commercialization within Islamic educational institutions. This study aims to integrate classical management functions with Qur’anic values in order to achieve sustainable falah in Islamic educational organizations. The research employs a qualitative library research approach using content analysis of Qur’anic verses related to management functions. The findings show that the principles of tauhid, syura, maslahah, and muraqabah strengthen management functions and create a balance between administrative effectiveness and spiritual values. This Islamic management model based on falah contributes to the development of more holistic and sustainable governance in Islamic education institutions